Las capacidades dinámicas y su influencia en la gestión empresarial de la Empresa INHARIPAC S.A. - Cedeño Santos, Melanie Nicole (2025)
The research was conducted with the objective of evaluating the dynamic capabilities and their influence on the business management of INHARIPAC S.A., for the contribution of competitive advantages. The methodology used was exploratory, field, bibliographic, descriptive and correlational, carried out in three phases. The first stage consisted of diagnosing the current state of the company through a business characterization matrix and evaluating the development of its dynamic capabilities; for this, an interview was applied to the general manager of the company and a structured survey with a Likert scale directed to the department heads, which was validated through the Delphi method, using a selection of indicators based on the Prism technique. In the second phase, the influence of dynamic capabilities on business management was determined and analyzed by applying a normality test and Spearman's correlation. The third phase involved the development of an action plan to strengthen the company's dynamic capabilities, carrying out an analysis of the identified problems with an Ishikawa diagram, and the design of improvement strategies using a 5W+1H matrix. The results identified weaknesses in the absorption, innovation and resilience capabilities, as well as in the organization, management and control processes. It is concluded that there is a positive, significant and perfect influence between the innovation and adaptation capabilities and planning and control, in contrast to the negative correlation of the resilience capacity.